KEBIJAKAN KRIMINAL DALAM MENGATASI KAMPANYE HITAM (BLACK CAMPAIGN) DI MEDIA SOSIAL - Irwan Hafid (Jurnal Bawaslu Provinsi Kepulauan Riau, 2020)
Misuse of social media during the election campaign is one thing that needs serious attention. In addition to promising various facilities, social media is also an effective means to commit a crime, such as the spread of hoax and black campaigns. That reality would be the basis for this writing. The theory used in this research is criminal policy theory and campaigns on socialmedia. While the method used is normative legal research with a statutory approach, a conceptual approach, and a comparative approach. The output of this paper is that the issue of legislation and coordination becomes a problem in the regulation of campaigns on social media. Therefore, this must be overcome through the efforts of penal and non-penal as part of criminal policy.